Knowledge, Attitudes and Practices of Prescribers towards Antimicrobial Stewardship at Hospitals in Khartoum State - Sudan - Salah Ali Alamin, Alneima; I. Kheder, Salah (Journal of Medical Informatics and Decision Making, 2020)
Introduction Antimicrobial stewardship (ASP) is of the utmost importance as a way to optimize the use of antimicrobials to prevent the development of resistance and improve patient outcomes. So, it is worthwhile to assess the knowledge, attitude and awareness regarding antimicrobial stewardship in hospitals. Objective The aim of this study is to assess knowledge, attitudes and practices (KAP) of prescribers towards antimicrobial stewardship at hospitals in Khartoum state and to identify the associations between prescriber’s demographic information and their knowledge. Methodology This descriptive cross-sectional study multi-centered study conducted in 10 hospitals at Khartoum state -Sudan, during period from November to December 2018. Study population included all prescribers who is available at study’s hospitals during study period and willing to participate in the study. A self-administered questionnaire addressing participants’ knowledge, attitudes, and practice (KAP) regarding antibiotic resistance and ASP distributed in the selected hospitals among attending house-officers, registrars and consultants completed then analyzed. Results Of the 294 medical staff targeted, 287 responded to the survey (response rate 97.6%). Only (26.4%) were familiar with the term ASP and (31.5%) claimed that it is effective in reducing resistance. (43.0%) of respondents believe that ASP play vital role on antibiotic prescribing. Only (9.5%) had ASP in their hospital and (13.5%) having policy and team. (45.3%) of participants had good level of knowledge about antimicrobial stewardship, but majority show negative attitude (63.1%), and poor practices (92.0%) regarding ASP. There was no observed correlation between knowledge and attitude, knowledge with practice (p-value ≥ 0.05). Only attitude with practice shows significance correlation (P=0.0001), which means that prescribers with positive attitude had the better practices towards antimicrobial stewardship. Age, occupation and experience are the only significant predictors of prescriber's knowledge and attitude towards antibiotic stewardship, while no association between these factors and practice. Conclusion The present study concludes that the knowledge of prescribers regarding ASP is moderate and their attitude is negative. Unfortunately, practices regarding ASP were poor, despite, the good knowledge regarding the effects of ASP on antimicrobial resistance.
Keywords: Antimicrobial stewardship; Resistance; Knowledge; Attitude; Practice; Sudan.